Peran Transformasi Digital Pada Pemasaran PTPN IV Pada Peningkatan Engagement Sosial Media - Muhammad Raihan Riza; Tamara Khaisya Maruhawa; Siti Azzahra Sinaga; Hasan Sazali (CV. ITTC INDONESIA, 2025)
Digital transformation has become a crucial element in corporate marketing strategies, particularly in enhancing social media engagement. This study analyzes the role of digitalization in PT Perkebunan Nusantara IV (PTPN IV)’s marketing strategy and its impact on customer engagement. Using a qualitative research approach through observation, documentation, and literature review, the findings indicate that implementing digital strategies—such as social media utilization, interactive content, and data analytics—significantly increases customer interaction and brand awareness. The results show that customer engagement improves through effective content strategies, influencer collaborations, and the use of social media analytics. However, challenges remain, including changes in social media algorithms and increasing digital competition. Therefore, companies must continuously develop data-driven strategies and optimize digital technology to maintain competitiveness and enhance customer loyalty.